How disinformation affects the organizations' performance in the digital era - Pinto, Cláudia; Braga, Inês; Martins, Susana; Carvalho, Milena (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2022)
It is crucial to understand how information, when well managed, becomes the primary factor of intelligence and competitive advantage of an organization. Information management makes an essential contribution to achieving the organization's mission and strategy, affirming its business or area of operation, making its human resources and tangible resources profitable. Information is therefore so indispensable to the organizations that they often structure and classify it based on its organization, its functions and activities, that is to say, based on documentary production, information flowsbetween departments, archiving and proof that this information constitutes. In 21st century organizations, where the digital paradigm is omnipresent, it’s crucial that the information manager be aware that misinformation and disinformation are real threats to quality information and that can jeopardizethe success of effective information management. Through the literature review, we intend to reflect on various theoretical issues, highlighting ideas and good practices to combat the danger of this negative reality. These include the need for all employees of an organization to have media literacy skills, which can be fostered and formally provided by the institution throughlifelong learning.